2019
DOI: 10.1109/access.2019.2944681
|View full text |Cite
|
Sign up to set email alerts
|

Wideband MIMO Antenna Array Covering 3.3–7.1 GHz for 5G Metal-Rimmed Smartphone Applications

Abstract: A wideband 8-antenna Multiple-Input Multiple-Output (MIMO) array covering 3.3-7.1 GHz for Fifth-Generation (5G) sub-7 GHz and New Radio Unlicensed (NR-U) applications in metal-rimmed smartphones is presented in this paper. In this design, the open slot loaded metal rim is directly fed by microstrip line. Hybrid Inverted-F Antenna (IFA) and slot modes are generated. Utilizing impedance matching and reactance loading, the two modes are moved and combined, so as to achieve size reduction and wideband coverage. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
61
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(67 citation statements)
references
References 48 publications
1
61
0
Order By: Relevance
“…Content may change prior to final publication. about 3300-7100 MHz is provided but isolation is comparatively low [121]. It is also observed that [123] provides isolation better than 13 dB.…”
Section: ) Multi-element With Metal Rim Antennamentioning
confidence: 89%
See 1 more Smart Citation
“…Content may change prior to final publication. about 3300-7100 MHz is provided but isolation is comparatively low [121]. It is also observed that [123] provides isolation better than 13 dB.…”
Section: ) Multi-element With Metal Rim Antennamentioning
confidence: 89%
“…In [121] along with wideband, the metal rim MIMO multielement antenna is characterized by reduced antenna size due to inverted-F antenna design along with tuning stubs. The multi-element antenna design consists of eight elements that cover 3.3-7.1 GHz and uses the FR4 substrate.…”
Section: ) Multi-element With Metal Rim Antennamentioning
confidence: 99%
“…1(a). The aim is to present a highly isolated MIMO antenna design with omnidirectional radiation patterns [22]- [24] at two targeted operating bands, i.e. 2.6 GHz and 3.5 GHz since these two bands are common for 4G and 5G applications.…”
Section: Configurations Of Mimo Antenna System and Tapered Slot Amentioning
confidence: 99%
“…Some MIMO antennas for 5G smartphone terminals have been proposed. The types of antenna elements selected are mainly inverted F antennas [7][8][9][10], loop antennas [11][12][13][14], and slot antennas [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%